Protective Effects of Melon Extracts on Bone Strength, Mineralization, and Metabolism in Rats with Ovariectomy-Induced Osteoporosis - Bongju Kim; Sung-Ho Lee; Su-Jin Song; Won Hyeon Kim; Eun-Sung Song; Jae-Chang Lee; Sung-Jae Lee; Dong-Wook Han; Jong-Ho Lee (MDPI AG, 2019)
A polyphenolic extract from melon (Cucumis melo L.), as a potential source of natural antioxidants, has been reported to have a positive effect on osteoblast activity. In this study, the protective effects of heat-treated melon extract (ECO-A) on bone strength, mineralization, and metabolism were examined in osteoporotic rat models. Osteoporosis was induced by ovariectomy (OVX) in female rats and then maintained for 8 weeks, along with the ingestion of phosphate-buffered saline (PBS, OVXP) or ECO-A (OVXE) for an additional 4 weeks. At a pre-determined timepoint, bone strengths, as well as bone mineral contents (BMC) and the density (BMD) of femurs and/or lumbar spines extracted from each animal, were measured by a mechanical test and dual-energy X-ray absorptiometry, respectively. Moreover, several biochemical markers for bone turnover were analyzed by respective colorimetric assay kits in addition to clinical analyses. The maximum load and stiffness of femurs from the OVXE group were found to be significantly higher than the other groups. Furthermore, the OVXE group showed significantly higher BMC, BMD, and bone volume than the OVX and OVXP groups, which were comparable to the non-OVX (sham) group. The levels of bone formation and resorption markers in the OVXE group were similar to the sham group, but significantly different from other groups. In conclusion, these results suggest that ECO-A can play potentially positive roles in the protection of bone loss in rats with OVX-induced osteoporosis.